2023
DOI: 10.1093/cvr/cvad118
|View full text |Cite
|
Sign up to set email alerts
|

Integrative human atrial modelling unravels interactive protein kinase A and Ca2+/calmodulin-dependent protein kinase II signalling as key determinants of atrial arrhythmogenesis

Abstract: Atrial fibrillation (AF), the most prevalent clinical arrhythmia, is associated with atrial remodeling manifesting as acute and chronic alterations in expression, function, and regulation of atrial electrophysiological and Ca2+-handling processes. These AF-induced modifications crosstalk and propagate across spatial scales creating a complex pathophysiological network, which renders AF resistant to existing pharmacotherapies that predominantly target transmembrane ion channels. Developing innovative therapeuti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…These results are consistent with our previous study suggesting that reported LTCC reduction by AF is an adaptive mechanism of the atria to limit triggered activity, whereas enhanced RyR2 phosphorylation constitutes a maladaptation that drives the arrhythmia. 28 In this regard, our suite of sex-specific human atrial cardiomyocyte models is unique and instrumental to gain mechanistic insights into the sex-dependent differences in Ca 2+ -driven arrhythmogenesis in human atria, providing a basis to inform putative treatment strategies to correct the deranged Ca 2+ signals, especially for the female atria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are consistent with our previous study suggesting that reported LTCC reduction by AF is an adaptive mechanism of the atria to limit triggered activity, whereas enhanced RyR2 phosphorylation constitutes a maladaptation that drives the arrhythmia. 28 In this regard, our suite of sex-specific human atrial cardiomyocyte models is unique and instrumental to gain mechanistic insights into the sex-dependent differences in Ca 2+ -driven arrhythmogenesis in human atria, providing a basis to inform putative treatment strategies to correct the deranged Ca 2+ signals, especially for the female atria.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies involving animals uncovered sex-dependent differences in upstream signals including cAMP/phosphodiesterase in the ventricles, 64,65 similar differences, if confirmed in the atria, can be readily incorporated into our framework, as established in our atrial signaling model. 28 Third, our current work solely focused on isolated cardiomyocytes. Previous studies associated female atria with greater fibrosis 44,66 as compared to male atria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations